Ce:LaB3O6 glass for high-resolution radiation dosimetry. (31st January 2022) - Yuan, Dongsheng; Víllora, Encarnación G.; Kato, Takumi; Nakauchi, Daisuke; Yanagida, Takayuki; Shimamura, Kiyoshi
Abstract: Ce:LaB3 O6 (LBO) glass, whose constituents are abundant elements and fabrication is easy and cheap, is found to be a promising thermoluminescence (TL) dosimeter. This is originally achieved by CeF3 doping and melting under a reducing atmosphere, with the optimum concentration of 0.1% (quantum efficiency = 66%). The corresponding Ce interatomic distance is ∼4 nm, below which concentration quenching occurs via Ce dipole–dipole interaction, as elucidated experimentally by Dexter's theory. Ce:LBO exhibits a good dose resolution, with a linear dependence covering five orders of magnitude on both irradiation-dose and TL-response. Furthermore, it can be cyclically irradiated and read without degradation.